IMPLEMENTASI MODEL PEMBELAJARAN TEAM GAME TOURNAMENT(TGT) UNTUK MENINGKATKAN AKTIFITAS BELAJAR SISWA - Prihastini Oktasari Putri; Erna Wati (Intersections, 2020)
This study aims to: (1) determine the responses of students in learning mathematics with a cooperative model type Team Game Tournament (TGT). (2) determine whether using the cooperative model type Team Game Tournament (TGT) can improve students' mathematics learning activities. The type of research used is Classroom Action Research (CAR). The sample in this study were all grade V students of SD Negeri 1 Plumbon in the academic year 2019/2020 as many as 24 students. The instruments used in this study were observation, documentation and questionnaires. Based on the results of the study, it was concluded that: (1) The fifth grade students of SD Negeri 1 Plumbon gave a positive response to the implementation of learning mathematics using the Team Game Tournament (TGT) cooperative model. (2) the use of the Team Game Tournament (TGT) type cooperative model can increase student learning activities in the fifth grade mathematics subject of SD Negeri 1 Plumbon. This increase can be seen in the results of the observation sheet and questionnaire. Based on the observation sheet, it was found that the average percentage increase in pre-cycle was 36.97% to 61.45% in cycle I and 72.39% in cycle II. Meanwhile, based on the student learning activity questionnaire using the cooperative type Team Game Tournament (TGT) model, it also increased from the pre-cycle by 61.97%, increased to 74.88% in cycle I and increased again in cycle II which was 80.20%.